1979
DOI: 10.1111/j.1600-0722.1979.tb00694.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative bone morphometric analysis of mandibles and 2nd metacarpals

Abstract: Wowern, N. v. Sc Stoltze, K.: Comparative bone morphometric analysis of mandibles and 2nd metacarpals. ScandJ. Dent. Res. 1979: 87: 358-364. Abstract -A comparative analysis of bone mass in the mandible and the metaearpal index: (D-d)/DS6 has been carried out on autopsy specimens of mandibles and standard hand radiographs from 40 subjects aged 20-90 years. Microradiograms of standardized lOO-jimthick sections of the undemineralized plastic embedded material from a standard site of the mandible were used for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…showed an increased remodeling [16][17][18][19][20][21], a decrease in bone volume of the mandible [22] and cancellous bone loss in the mandibular condyle [23]. The estrogen deficiency-induced osteoporosis appears to be a result of the binding of the receptor activator of the nuclear factor B (RANK) and RANK ligand (RANKL), as previously reported [24][25][26].…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…showed an increased remodeling [16][17][18][19][20][21], a decrease in bone volume of the mandible [22] and cancellous bone loss in the mandibular condyle [23]. The estrogen deficiency-induced osteoporosis appears to be a result of the binding of the receptor activator of the nuclear factor B (RANK) and RANK ligand (RANKL), as previously reported [24][25][26].…”
Section: Introductionmentioning
confidence: 63%
“…Thus, reduced-sclerostin did not appear to be associated with diminished ER in osteocytes in the mesial region. Other studies suggested a proapoptotic effect of estrogens on osteoclasts and osteoblasts [43,44], and therefore, it was necessary to confirm whether the reduced amount of sclerostin would be It is well known that OVX stimulates osteoclastic differentiation and subsequent bone resorption in long bones, and also shows the similar effects in alveolar bone [16][17][18][19][20][21][22].…”
Section: Immunolocalization Of Er and Tunel-positive Osteocytes In Tmentioning
confidence: 99%
“…36 Using yet another metacarpal index, other investigators found significant correlations between the index and mandibular cortical porosity and cortical width for forty male and female cadavers (20 to 90 years of age). 37 In a two article series (1974), specific gravity analysis (as determined by water displacement), dual-beam Xray analysis, and activation analysis indicated that for 50 cadaver mandibles and radii (1) there were significant decreases in densities with age, (2) the densities in the mandibles were significantly correlated with those of radii, and (3) the densities of female mandibles were significantly lower (by 8%) than those for males. 38 · 39 Single photon absorptiometry (SPA), which was introduced in 1963 and uses 125-iodine as an energy source, 40 was employed in 1977 to determine forearm bone mineral content (BMC) in 15 patients with juvenile periodontitis and fifteen controls.…”
Section: Osteoporosis and Oral Bone Lossmentioning
confidence: 95%
“…Several investigators [6][7][8][9][10][11] have also reported a positive correlation between the general skeletal bone mass or bone mineral density (BMD) and the mandibular bone mass in postmenopausal women. Von Wowern and Storze 7 demonstrated by bone morphometry that the buccal cortical bone mass of the mandible was significantly correlated with the metacarpal index.…”
mentioning
confidence: 98%